Kara ograniczenia wolności w systemie środków reakcji karnej. Rozważania aksjologiczne i polityczno-kryminalne - Zalewski, Wojciech (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The beginning of the 21st century has been marked by technicisation of sentencing, development of biometry, managerialism in sentencing and privatisation of sentence enforcement. As if on the margins of the main process there are attempts to find alternatives to the old paradigm, especially in the form of remedial justice. The present paper is an analysis of the axiological assumption, international experiences as well as selected foreign and Polish solutions concerning remedies based on local community work. Experiences with applying this form of sentencing demonstrate its advantages: staying in touch with one’s milieu, self-discipline, flexible sentencing and costs of organisation. If the remedy is to be perceived as a form of punishment, it is important for the work performed by the sentenced offenders to be genuinely beneficial to society.
Keywords: praca społeczna lub praca; penologia menedżerska; humanizm orzekania